Application of the Problem Based Learning Model to Improve Chemistry Learning Outcomes for Class X SMK Negeri 2 Palembang - Mustika Mustika; Muhammad Hadeli L; Meidia Farlina (Pedagogy Review, 2022)
Abstract: The implementation of Problem Based Learning model to increase students learning outcomes in tenth grade of SMK Negeri 2 Palembang. This study aims to improve student learning outcomes using learning Problem Based Learning (PBL) method. Research was done by two cycle and every cycle conducted two meetings with including planning stage, implementation, observation, and reflection. Subject of research is thirty four students of X grade of SMK Negeri 2 Palembang. The instrument used is observation sheet for both learners and learning outcome test. The result of the study is students learning outcomes increase with 44,118% classical completeness in first cycle and 85,294% in the second cycle. The result is supported by students activity during learning process. In the first cycle, the percentage in the first meeting is 53,6332% and in the second meeting is 57,2664%. In the second cycle, first meeting is 64,1869% and in the second meeting is 69,3772%. Based on the result of research showed that the Problem Based Learning can improve students learning outcomes in the X grade students of TITL 3. Keywords: class treatment study, problem based learning, results of students learning